Clinical disorders of bone resorption. - Russell, G; Mueller, G; Shipman, C; Croucher, P (2001)
Clinical disorders in which bone resorption is increased are very common and include Paget's disease of bone, osteoporosis, and the bone changes secondary to cancer, such as occur in myeloma and metastases from breast cancer. Clinical disorders of reduced bone resorption are less common and often have a genetic basis, e.g. in osteopetrosis, and in pycnodysostosis due to cathepsin K deficiency. Bone is metabolically active throughout life. After skeletal growth is complete, remodelling of both cortical and trabecular bone continues and results in an annual turnover of about 10% of the adult skeleton. The commonest disorder of bone resorption is osteoporosis, which affects one in three women over 50 years. Its pathophysiological basis includes genetic predisposition and subtle alterations in systemic and local hormones, coupled with environmental influences. Treatment depends mainly on drugs that inhibit bone resorption, either directly or indirectly. This includes bisphosphonates, oestrogens, synthetic oestrogen-related compounds (SERMs--selective oestrogen receptor modulators) and calcitonin. The most widely used drugs for all disorders of increased bone resorption, including osteoporosis, are the bisphosphonates. Recent elucidation of their mode of action, together with the rapidly increasing knowledge of regulatory mechanisms in bone biology, offers many opportunities for the development of new therapeutic agents.